(untitled) (Medical Forum Monthly, 2024)
Objective: This study was designed to assess the accuracy of lung ultrasound (LUS) in the diagnosis of pneumonia in children in comparison to chest X-ray. Study Design: Randomized controlled trial study Place and Duration of Study: This study was conducted at the Pediatrics Medicine Ward, King Edward Medical University/Mayo Hospital, Lahore from August 2016 to February 2017. Materials and Methods: A total of 282 patients fulfilling the inclusion criteria were enrolled and underwent clinical examination, chest radiograph (AP view, interpreted by a Paediatric radiologist blinded to the sonography results), lung ultrasound (by a pre-specified hospital radiologist) and blood sample analysis in the first 24 hours after admission. The accuracy of US in diagnosing pneumonia (i.e. its sensitivity, specificity, and positive and negative predictive values) was compared with that of chest radiographs Results: A total of 48 patients had radiographically confirmed community acquired pneumonia (CAP). The sensitivity, specificity, and positive and negative predictive values of LUS in comparison with chest radiograph (CR) were respectively 95.5%, 90.0%, 99.6%, 42.8%. Conclusion: LUS identified a significantly higher number of cases indicating that it’s also a sensitive tool in comparison of chest radiography in the diagnosis of pneumonia in children although its effectiveness in determining the type of lung involvement requires further evaluation.